Riquezas da fé: um tour pelas igrejas históricas de Minas Gerais - BRITO, Clemilda Monteiro de Almeida; SILVA, Ana Maria da; LIMA, Carla Regina Nunes; OLIVEIRA, Gisele de; GIANNONI, Giovana Munhoz; SILVA, Isaque Mateus de Melo (CETEC – GEEAD (Unidade de Ensino Médio e Técnico- Grupo de Estudo de Educação à Distância ), 2024)
Este trabalho de conclusão de curso propõe a criação de um roteiro de turismo religioso em Minas Gerais, integrando conhecimentos do curso técnico em Guia de Turismo EAD. Com base na importância histórica e cultural do estado, o roteiro oferece uma experiência imersiva em cidades históricas, valorizando o patrimônio religioso, arquitetônico e cultural. Destinado a diversos perfis de turistas, o projeto combina turismo de fé com outras modalidades, como o gastronômico e o cultural. A proposta é realizar uma viagem de quatro dias durante o feriado de abril de 2025, aliando qualidade, significado e custo acessível.

This final course project proposes the creation of a religious tourism itinerary in Minas Gerais, integrating knowledge acquired during the Technical Course in Tourism Guide (EAD). Based on the historical and cultural significance of the state, the itinerary offers an immersive experience in historic cities, highlighting religious, architectural, and cultural heritage. Aimed at various tourist profiles, the project combines faith-based tourism with other modalities, such as gastronomic and cultural tourism. The proposal is to carry out a four-day trip during the April 2025 holiday, combining quality, meaningful experiences, and affordable cost.
Richness of faith: a tour of the historic churches of Minas Gerais
Keywords: Turismo religioso; Arte sacra; Turismo cultural; Turismo, Hospitalidade e Lazer